Assessment In Translation Studies: Research Needs - Martínez Melis, Nicole; Hurtado Albir, Amparo (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractOn the whole, most research into assessment in translation only concentrates on one area — evaluation of translations of literary and sacred texts — and other areas are ignored. In fact, this field of research includes two other areas, each with its own characteristics: assessment of professionals at work and assessment of trainee translators.Starting with this presupposition, we describe the three areas and analyze the notion of translation assessment, so as to define the characteristics of each area: objects, types, functions, aims and means of assessment. Next, we discuss the question of translation competence, and the concepts of translation problems and translation errors, in order to reach a general principle that should be applied in all assessment. Finally, we suggest assessment instruments to be used in teaching translation and make suggestions for research in assessing translator training, an area that has long been neglected and deserves serious attention.